(untitled) (Community Based Medical Journal, 2025)
The recent COVID-19 outbreak has impacted the delivery of healthcare and interventional cardiology services worldwide. Several studies conducted in different countries have revealed that there was a significant reduction in performing percutaneous coronary intervention (PCI) procedures during the onset of the pandemic; however, the situation of such interventional practice n Bangladesh is not well documented. Hence, this study aims to investigate the changes in the volume of interventional cardiology services before and during the COVID-19 outbreak in a tertiary level healthcare facility of the country. This retrospective study based on record review involved 304 patients admitted into Mugda Medical College Hospital, Dhaka, Bangladesh, between April 2019 and April 2021. The patients were categorized as group A (pre-COVID; N=170) and group-B (COVID; N=134) patients. Data were obtained on patient demographics, risk factors, medical history, type of intervention, and readmission of the patient. The pandemic period had an increased number of patients aged ≥60 years (51.5% vs. 42.9%) and a significant shift in gender distribution (16.4% male vs. 78.2% pre-pandemic). The ST elevation myocardial infarction (STEMI) remains relatively stable between the two groups (60.0% vs. 59.7%; p>0.05). Rates remained stable (40.3% vs. 40.0%; p<0.001). Similarly, the number of non-ST elevation myocardial infarction (NSTEMI) cases also remains unchanged (40.0% vs. 40.3%; p>0.05). An increase in balloon angioplasty procedure was observed during the pandemic (49.41% vs. 62.69%; p<0.001). In contrast, there was a huge decrease in angioplasty with stent procedure (42.35% vs. 21.64%; p<0.001). Patient readmission rate slightly decreased (18.82% vs.16.42%; p>0.05). This study highlighted that the COVID-19 outbreak brought changes in the patient population and interventional procedures in interventional cardiology at Mugda Medical College Hospital, Dhaka, Bangladesh. These figures are rather stable in STEMI cases, contrary to the tendencies in other countries, whereas the transition to balloon angioplasty most likely tried to reduce the time of the procedure. Thus, they stress the imperativity of context-sensitive approaches to cardiovascular health management during epidemics and call for additional research on later consequences. CBMJ 2025 January: Vol. 14 No. 01 P: 40-45